Vojaška bolnišnica v Kamniku in Mekinjah v času prve svetovne vojne - Hančič, Damjan (Kronika (Ljubljana), 2021)
The article presents the operations of the military hospital in Kamnik and Mekinje during the First World War. In Mekinje, the wounded were housed in several buildings and the main part of the hospital operated on the premises of the local Ursuline monastery. For a while, some of the wounded were also accommodated in four buildings in the nearby Kamnik, more specifically, in three buildings in the town centre and on the premises of the temporarily vacated Kamnik Gunpowder Factory for a little over a year. While undergoing treatment for various injuries and wounds sustained in the battlefield, the soldiers also contracted a number of contagious diseases, such as malaria or fatigue, cholera, typhus, and various fevers. During the war, the Kamnik area also housed many military units headed to the Isonzo Front. At the end of 1918, the area was further affected by the Spanish flu, which did not claim many lives.
Keywords: contageous diseases; Kamnik; Mekinje; military hospitals; nalezljive bolezni; ranjenci; Slovenia; Slovenija; svetovna vojna 1914-1918; vojaške bolnišnice; World War 1914-1918; wounded